On some geometric properties of sequence spaces of generalized arithmetic divisor sum function - Mursaleen, Mohammad; Herawati, Elvina (Journal of inequalities and applications, 2024)
Recently, some new sequence spaces ℓ p ( A α ) ( 0 < p < ∞ ) , c 0 ( A α ) , c ( A α ) , and ℓ ∞ ( A α ) have been studied by Yaying et al. (Forum Math., 2024 , https://doi.org/10.1515/forum-2023-0138 ) as matrix domains of A α = ( a n , v α ) , where a m , v α = { v α ρ ( α ) ( m ) , v ∣ m , 0 , v ∤ m , and ρ ( α ) ( m ) : = sum of the α th power of the positive divisors of m ∈ N . They obtained their duals, matrix transformations and associated compact matrix operators for these matrix classes. This article deals with some geometric properties of these sequence spaces.